3D reconstruction of plasma electrolytic oxidation coatings on Mg alloy via synchrotron radiation tomography. (15th July 2018) - Lu, Xiaopeng; Blawert, Carsten; Tolnai, Domonkos; Subroto, Tungky; Kainer, Karl Ulrich; Zhang, Tao; Wang, Fuhui; Zheludkevich, Mikhail L.
Highlights: 3D microstructure of PEO coated Mg is unveiled via synchrotron tomography. The pores characteristics has been qualitatively and quantitatively investigated. The coating porosity has a huge potential to store functional materials. Abstract: Plasma electrolytic oxidation (PEO) is a well-known surface treatment for Mg alloys, while high porosity is an issue to achieve long-term corrosion protection. Nevertheless, the presence of inherent porosity can be turned into advantage while used as nano/micro-structured reservoir of corrosion inhibitors or functional agents next to Mg surface providing an active corrosion protection and multi-functionality. For the first time, we report here the 3D internal architecture of PEO coated Mg via synchrotron-based microtomography. The pore characteristics have been qualitatively and quantitatively investigated to unveil the formation of the coating porosity and potential incorporation of functional elements in the pores.